The jurnal ANALISA JARINGAN WIRELESS MENGGUNAKAN METODE WARDRIVING MENGGUNAKAN TOOLS WIGLE WIFI WARDRIVING PADA KOMINFO SDDPI: ANALISA JARINGAN WIRELESS MENGGUNAKAN METODE WARDRIVING MENGGUNAKAN TOOLS WIGLE WIFI WARDRIVING PADA KOMINFO SDDPI - Buntoro, Vierly Unggul (JUPIK : Jurnal Penelitian Ilmu komputer, 2024)
This thesis presents a comprehensive analysis of wireless networks utilizing the wardriving method, employing the Wigle WiFi Wardriving tool, within the premises of the Indonesian Ministry of Communication and Informatics (Kominfo) and the Indonesian Telecommunications Regulatory Authority (SDPPI). Wardriving involves the systematic scanning of wireless networks by navigating through designated areas to identify, catalog, and assess the characteristics of these networks.The research encompasses data collection through the application of the Wigle WiFi Wardriving tool, capturing essential information regarding the wireless networks encountered within the Kominfo and SDPPI facilities. Subsequently, the collected data undergoes rigorous analysis, enabling an in-depth examination of network functionality, signal strengths, encryption methods, security protocols, and potential vulnerabilities.The study's outcomes yield valuable insights into the status, security, and efficiency of wireless networks operating within the Kominfo and SDPPI domains. This information empowers decision-makers to enhance network security measures, rectify weaknesses, and optimize wireless network infrastructure. Furthermore, the research underscores the significance of robust network security practices within governmental institutions, highlighting the need for constant monitoring and proactive measures to safeguard against potential threats.In conclusion, this study contributes to the broader understanding of wireless network security, with practical implications for improving network performance and ensuring data integrity in government entities. Keyword: Network,Security,Wi-Fi